2014
DOI: 10.5644/ama2006-124.110
|View full text |Cite
|
Sign up to set email alerts
|

First-year dental students’ motivation and attitudes for choosing the dental profession

Abstract: Independence, financial security and 'prestige' were the predominant motivating factors in this group of first-year dental students. Determining the reasons for choosing dentistry has important implications for the selection and training of students as well as for their future job satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 13 publications
(18 reference statements)
5
15
0
1
Order By: Relevance
“…Similar viewpoints about the dental profession were reported by Indian 1,9 and Bulgarian dental students. 10 The prestige of being a dental professional was also the dominant reason for choosing dentistry as a career amongst Iranian students. 2 Students from universities in Lithuania and Poland reported that the strongest influence they felt towards choosing to study dentistry was from their parents or relatives.…”
Section: Discussionmentioning
confidence: 99%
“…Similar viewpoints about the dental profession were reported by Indian 1,9 and Bulgarian dental students. 10 The prestige of being a dental professional was also the dominant reason for choosing dentistry as a career amongst Iranian students. 2 Students from universities in Lithuania and Poland reported that the strongest influence they felt towards choosing to study dentistry was from their parents or relatives.…”
Section: Discussionmentioning
confidence: 99%
“…This study went beyond previous research in three ways. First, while quite a number of studies have researched the career choice motivations of dental students [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and dental hygiene students, [22][23][24][25][26][27][28] only one previous study had explored how dental Table 3. Career choice motivations of students, by percentages of total responding dental students (N=783) and dental hygiene students (N=256) Note: Chi-square tests were used to compare the percentages of dental versus dental hygiene students' answers in each category.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Cohen and Coburn analyzed the relevance of various career choice reasons and found that the autonomy aspects of dentistry were no longer at the forefront of reasons why students wanted to become dentists. [11][12][13][14][15][16][17][18][19][20][21] Over the past three decades, research also focused on analyzing dental hygiene students' career choice motivations. [7][8][9][10] In those studies, students' motivations began to shift from materialistic to post-materialistic reasons, such as having favorable hours, and increasing numbers of students mentioned a desire for working with people.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several factors may govern or modulate the decision of pursuing this field. Traditionally, several factors have been recognized that may influence one's decision to choose dentistry as a future career including oral health promotion, assisting and working in societies, availability and ease of employment, financial security, prestige, provision of enough time off for family life, desire to work in health care and making a good income [2][3][4][5][6] . Interestingly, variation in social background, race, gender and country have been found to influence career selection as well [7][8][9][10] .…”
mentioning
confidence: 99%